Reactions of some sweet sorghum genotypes to Meloidogyne javanica e Pratylenchus brachyurus - Sharma, Ravi Datt; Medeiros, Antonio Carlos de Souza (Pesquisa Agropecuaria Brasileira, 2014)
Sixteen sweet sorghum genotypes were screened for resitance to Melaidogyne javanica and Pratylenchus brachyurus in a greenhouse with a temperature range of 25 to 28 °C. Evaluations for rool galls, egg mass development of M. javanica and final populations of both nematode species in soil and in roots and plant growth were made separately for each container 54 days after inoculations genotypes BR 601, CMS x S 733, BR 502, SART, CMS x S 734 and BR 503 were highly resistant; BR 501 and CMS x S 719 as resistant; CMS x S 735, BR 500, CMS x S 623, CMS x S 516, BR 602 and CMS x S 603 as moderately resistant to M. javanica. All the genotypes were susceptible to P. brachyurus except SART, which is moderately resistant. Out of the four genotypes CMS x S 734, BR 503, CMS x S 719 and CMS x S 732 tolerant to P. brachyurus, only genotype CMS x S 732 is also tolerant to M. javanica.